1986
DOI: 10.1679/aohc.49.449
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopic observation of the primary cilium in the pancreatic islets.

Abstract: Summary.A primary cilium often projected from the Golgi region of pancreatic A, B and D cells.The proximal portion of the cilium was found surrounded by a tubular invagination of the plasmalemma, and then the cilium extended into the intercellular canaliculus. The most proximal portion of the ciliary membrane exhibited periodical densities which might correspond to the ciliary necklace.The axoneme of the cilium was basically of the 9+0 pattern, i.e., nine peripheral doublets and no central singlet, though it w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
40
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 19 publications
1
40
0
Order By: Relevance
“…Bars 20 μm lation or via intercellular spaces to act upon other islet cells in a paracrine manner. Some morphologists have recognized the development of a special intercellular canalicular system apart from the perivascular spaces within pancreatic islets (7,39). As shown by the present SEM observation, the primary cilia were usually located in these intercellular canalicules, i.e., microvillous channels among islet cells, but did not face the perivascular spaces.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Bars 20 μm lation or via intercellular spaces to act upon other islet cells in a paracrine manner. Some morphologists have recognized the development of a special intercellular canalicular system apart from the perivascular spaces within pancreatic islets (7,39). As shown by the present SEM observation, the primary cilia were usually located in these intercellular canalicules, i.e., microvillous channels among islet cells, but did not face the perivascular spaces.…”
Section: Discussionmentioning
confidence: 50%
“…Therefore, an interesting inquiry to be addressed in future studies is whether BBS patients and BBS protein-knockout mice normally express SSTR3 on the primary cilia of insulin cells. Cells of pancreatic ducts and islets possess the primary cilia, but acinar cells of the exocrine pancreas apparently lack them (1,5,22,39). An electron microscopic study by Yamamoto and Kataoka (39) has reported in detail the ultrastructure of primary cilia on islet cells of some animal species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endocrine cells also possess primary cilia in the adenohypophysis, pancreatic islets, and adrenal gland. Electron microscopic studies of these endocrine cells have demonstrated the existence of single cilia which display a structural organization unlike that of the motile cilia (5,45,49). Our recent immunohistochemical study revealed an abundance of SSTR3-expressing solitary cilia in growth hormone (GH)-secreting cells and insulin-secreting β-cells of the mouse (24).…”
mentioning
confidence: 92%
“…In addition, the structural relationship between the primary cilium and the Golgi complex and the presence of the small secretory vesicles near the membrane of the ciliary pocket of the differentiating cilia might also indicate the participation of these structures in secretory processes during the early stages of thyroid development. Similarly, primary cilia have frequently been found in the endocrine cells of the pancreas (Yamamoto and Kataoka, 1986;Bertelli and Regoli, 1994;Aughsteen, 2001) and some authors have suggested that they are probably involved in secretory processes (Aughsteen, 2001). The involvement of cilia in secretory processes was also demonstrated in a study that described the anatomical interrelationship between the primary cilium, the Golgi apparatus of chondrocytes and smooth muscle cells (Poole et al, 1997).…”
Section: Discussionmentioning
confidence: 89%